Factors influencing EFL students’ speaking anxiety: A pedagogical review - Agispa Agis; Vivi Tamara; Sri Wahyuni (Universitas Pakuan, 2026)
Speaking is a vital skill in English learning, enabling individuals to express ideas, emotions, and information effectively. However, many students experience fear and anxiety when speaking in English, particularly in front of others. Gap in literature of this study is a previous studies have mostly examined linguistic or psychological factors separately, overlooking how these elements interact to influence speaking performance. Purpose of the study is this research aims to identify the intrinsic and extrinsic causes of students’ fear of speaking English and to analyze effective pedagogical and psychological strategies for reducing speaking anxiety. Method of this study is using a library research design, this study analyzed theoretical and empirical literature from 2019–2024 related to speaking anxiety, fear of public speaking, and EFL pedagogy. The results indicate that speaking fear is influenced by intrinsic factors, such as low proficiency, low confidence, and fear of negative evaluation and extrinsic factors, including unsupportive classroom environments and peer pressure. Collaborative approaches, like peer teaching and peer feedback, were found to effectively reduce anxiety and increase students’ confidence in speaking. Conclusion the study concludes that overcoming speaking anxiety requires integrating psychological and pedagogical approaches. Creating a supportive classroom environment and promoting collaboration can significantly enhance students’ confidence and speaking performance in English.